Reflections on the conceptualisation and practices of community engagement as a core function of universities - Saidi, A. (South African Journal of Higher Education, 2023)
The world saw the “human” side of universities during the Covid-19 pandemic as universities across the globe were at the forefront of efforts to control the spread of the Coronavirus, and to explore means of making the human population acquire immunity against the virulent disease. This article contends that, although this appeared as unusual, the universities were simply fulfilling their obligation to humanity because the raison d’être of universities includes being of service to society. Therefore, if they are unable to prevent crises from setting in, they should at least be at the forefront of efforts to combat the crises, and mitigate their effects on people. The article seeks to set the scene for the collection of articles that follow in this special issue of the South African Journal of Higher Education (SAJHE) on the theme of community engagement as a core function for universities. It argues that universities have social responsibility, and they should therefore serve as anchors of towns and regions; as engines of development in their respective geographical areas; and as champions of social causes. It presents and discusses the concepts and practices of community engagement that are critical to understanding the arguments and counterarguments in the articles that follow. These include the relationship between community engagement, on the one hand, and transformation of higher education as well as decolonisation of knowledge and ways of knowing, on the other. The article also reflects on the state of community engagement in universities in South Africa, and explains that it is mostly regarded as a stepchild because it is not valued, funded or supported in the same way as the other two core functions of teaching and learning, and research and innovation. The article also cautions against the use of rhetoric to romanticise community engagement when the projects on the ground leave much to be desired, and with not potential to make a difference to society.